Powieść milicyjna - reaktywacja = Militia crime stories: a revival - Brylla, Wolfgang J. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Militia crime novel, which was a dominant subgenre of the novel in the years of the Polish People`s Republic (1952-1990), has recently been revived mainly due to Ryszard Ćwirlej`s work. Nevertheless, in the period mentioned those novels were not much appreciated by critics.`
Keywords: powieść milicyjna; powieść kryminalna; literatura polska - 21 w.